(untitled) (Experimental biology, 2022)
Theriological studies of the Teniz - Korgalzhyn region are covered rather sparsely in the literature and are fragmentary, since the Korgalzhyn Reserve mainly has an ornithological direction. The purpose of this article is to study the current state of the species composition of mammals of the Teniz-Korgalzhyn region and make the necessary additions to it. The research work was carried out for the period from 2016-2021. The authors of the article, based on the actual research conducted on the inventory of mammalian species in the reserve, prove the presence of local populations of species not previously noted on the territory of the reserve and include them in the inventory list of the theriofauna of the reserve. The material was collected on the territory of the Korgalzhyn State Nature Reserve and in its surroundings. Literary and intradepartmental data were also used. To include a new species in the list of local theriofauna and to distinguish individual visits of animals from the formation of a local population in the study area, 2 criteria were used: frequency and geography of encounters, and breeding of offspring. Of the 4 species new to the region, 2 species are native to Kazakhstan (Siberian roe deer, yellow gopher). Their presence in the region is insignificant and probably does not have a negative impact on the existing ecosystem of the region. The greatest concerns are caused by 2 acclimatizant species, namely the American mink, raccoon dog. Which are recognized as invasive species in Russia and Kazakhstan. The possibilities of the distribution and reproduction of these species in the territory they have developed and the possible impact on the native fauna of the region are also analyzed.